1996
DOI: 10.1200/jco.1996.14.1.268
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II trial comparing different doses of the bisphosphonate ibandronate in the treatment of hypercalcemia of malignancy.

Abstract: Ibandronate therapy led to a dose-dependent reduction in serum calcium levels. The response to ibandronate treatment correlated negatively with the initial serum calcium level and positively with the dose administered. A dose of 2 mg was necessary to achieve a response rate comparable to that in previous studies with the bisphosphonates pamidronate and clodronate. Because the incidence of drug-associated AEs was low, a dose escalation of ibandronate can be recommended for further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…Normocalcemia was maintained for up to 36 days following treatment. Doses ≥2 mg were comparable in efficacy with pamidronate and clodronate, and serious adverse events were minimal (three reports from 174 patients), consisting of fever, nausea, and thrombocytopenia [50].…”
Section: Nitrogen-containing Bisphosphonatementioning
confidence: 99%
See 1 more Smart Citation
“…Normocalcemia was maintained for up to 36 days following treatment. Doses ≥2 mg were comparable in efficacy with pamidronate and clodronate, and serious adverse events were minimal (three reports from 174 patients), consisting of fever, nausea, and thrombocytopenia [50].…”
Section: Nitrogen-containing Bisphosphonatementioning
confidence: 99%
“…Ibandronate, a newer nitrogen-containing bisphosphonate, was similarly effective in two large phase II trials [49,50], significantly lowering serum calcium levels in up to 77% of patients after 5 days. Normocalcemia was maintained for up to 36 days following treatment.…”
Section: Nitrogen-containing Bisphosphonatementioning
confidence: 99%
“…Doses of 2, 4, and 6 mg had success rates of 50%, 76%, and 77%, respectively (44). Compared with pamidronate, the duration of response is longer with ibandronate (50).…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…Randomized clinical trials with pamidronate, zoledronate, and ibandronate have all shown efficacy in the treatment of hypercalcemia of malignancy (42)(43)(44). However, the three bisphosphonates differ in terms of their potency and risk for toxicity.…”
Section: Bisphosphonatesmentioning
confidence: 99%
See 1 more Smart Citation